Tissue-type plasminogen activator in the ischemic brain: more than a thrombolytic - Yepes, Manuel; Roussel, Benoit D.; Ali, Carine; Vivien, Denis (Trends in neurosciences (Regular ed.), 2009)
Thrombolysis with tissue-type plasminogen activator (tPA) is used for the treatment of patients with acute ischemic stroke. However, a growing body of evidence indicates that, besides the unquestionable benefit from its thrombolytic activity, tPA also has a deleterious effect on the ischemic brain including cytotoxicity and increased permeability of the neurovascular unit with the development of cerebral edema. Because an increasing number of acute stroke patients are treated with tPA, it is important to know the mechanisms of harmful effects of tPA on the ischemic brain. Here, the best studied pathways of tPA neurotoxicity are discussed along with future directions for a safer use of tPA as a thrombolytic agent in the setting of acute ischemic stroke.